Effect of the strategy of the scientific stations in the achievement and some science operations in the science of the sixth grade pupils in the primary city of Mecca - Al Zahrani, Azza Saleh (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to investigate the impact of scientific stations on academic achievement and the development of the skills of scientific processes in science among sixth grade students in the life processes unit.In order to achieve this, the researcher followed the semi-experimental approach based on the design of the two groups: experimental and control, and designed a test for the achievement of the study and test for the operations of science, and two teaching materials are the teacher's guide and the workbook of the activities of the student, and after the validation of the tools and stability were applied to the study sample, A student was divided into two groups: an experimental group (40) students were taught the unit of life processes using scientific stations, and a control group (41) students were taught with the unit in the usual way. The data were treated using T test for two independent groups Effect size, Pearson correlation coefficient.The results of the study were as follows: There were differences between the mean of the experimental and control groups in the post-measurement of the achievement test (levels and the total score), as well as in the test of the processes of science (operations and the total score) for the experimental group. , Science operations are great, and there is a relationship between achievement and science processes.In light of the findings of the research, a number of recommendations were presented, including the use of scientific stations in science teaching, the training of female teachers in the service, and the training of female students in the faculties of education.
Keywords: scientific stations; academic achievement; science processes